Integration of Genetic and Process Engineering for Optimized Rhamnolipid Production Using Pseudomonas putida - Tiso, Till; Ihling, Nina; Kubicki, Sonja; Biselli, Andreas; Schonhoff, Andreas; Bator, Isabel; Thies, Stephan; Karmainski, Tobias; Kruth, Sebastian; Willenbrink, Anna-Lena; Loeschcke, Anita; Zapp, Petra; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Rhamnolipids are biosurfactants produced by microorganisms with the potential to replace synthetic compounds with petrochemical origin. Possible industrial applications range from pharmaceuticals to bioremediation agents. As the challenges to intensify recombinant rhamnolipid production from sugars are manifold, multidisciplinary approaches are required. Previously, P. putida KT2440 was developed as heterologous platform strain for rhamnolipid synthesis. Based on this, a multidisciplinary approach towards developing a sustainable rhamnolipid production process is presented. This includes strain development and physiological characterization, improvement of cultivation conditions, and downstream processing as well as life cycle assessment (LCA). Newly developed expression cassettes for stable integration of the rhamnolipid biosynthesis genes into the genome outperformed plasmid-based expression systems. Furthermore, genetic stability of the production strain was improved by using an inducible promoter. To enhance rhamnolipid synthesis, energy and/or carbon consuming traits were removed: Mutants negative for the synthesis of the flagellar machinery or the storage polymer PHA showed increased production by 50 %. A scale-up from shake-flasks was carried out using a 1 L bioreactor. By recycling of the foam, biomass loss could be minimized and a rhamnolipid titer of up to 1.5 g/L was achieved without using mechanical foam destroyers or anti foaming agents. The usage of a suitable minimal medium reduced undesired interphase formation in the liquid-liquid extraction step. To assess the relevant system variants by their environmental impacts, a technical scale production process was designed (150 L fermentation volume) and evaluated performing LCA. The process chains and their specific environmental impact were examined. It was found that next to biomass supply, the fermentation had the biggest environmental impact. The results are discussed in the context of the challenges of microbial biosurfactant production using hydrophilic substrates on an industrial scale, and how a multidisciplinary approach can be guided by early process evaluations.